Effect of new generation enzymes addition on the physical, viscoelastic and textural properties of traditional Mexican sweet bread. (January 2018) - Barbosa-Ríos, J.A.; Castillón-Jardón, J.; Guadarrama-Lezama, A.Y.; Alvarez-Ramirez, J.; Meraz, M.; Carrillo-Navas, H.
Abstract: The effect of adding new generation enzymes (0.25, 0.5, 0.75, and 1.0% w/w) on traditional Mexican sweet bread physical, viscoelastic (elastic and plastic work) and textural properties was studied. Physical properties as weight lost, pore uniformity, color, etc., improved with enzyme addition. Viscoelasticity properties were analyzed by uniaxial compression test under small strain, showing that the use of small enzyme fractions (∼0.25–0.5% w/w) are enough to enhance mechanical behavior (higher elastic work) and cohesiveness and resilience parameters after four storage days. This trend suggests a mechanism related to pore distribution and an equilibrium crust-crumb that lead to improved bread freshness over storage period. Overall, results indicated that relatively low enzyme concentrations can led to important improvements in the fabrication process of traditional Mexican sweet bread. The proposed enzyme concentrations are as small as 0.25–0.3% w/w, corresponding to approximately half the percentage of the amount frequently used in industrial bread production. Highlights: Addition of enzymes in traditional Mexican sweet bread improved bread making. Baking time curves presented three stages in bread making process. Pore size heterogeneity increased with concentration of new generation enzymes. Incorporation of enzymes enhanced the softness in the bread microstructure. Staling effect was retarded with addition of new generation enzymes.